Are Levels of NT‐proBNP and SDMA Useful to Determine Diastolic Dysfunction in Chronic Kidney Disease and Renal Transplant Patients?. Issue 6 (November 2013) - Memon, Lidija; Spasojevic‐Kalimanovska, Vesna; Stanojevic, Natasa Bogavac; Kotur‐Stevuljevic, Jelena; Simic‐Ogrizovic, Sanja; Giga, Vojislav; Dopsaj, Violeta; Jelic‐Ivanovic, Zorana; Spasic, Slavica
<x xml:space="preserve">Abstract</x> Background The aim of the study was to determine the clinical usefulness of N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP) and symmetric dimethylarginine (SDMA) for detection of renal and left ventricular (LV) diastolic dysfunction in chronic kidney disease (CKD) patients and renal transplant (RT) recipients. Methods We included 98 CKD and 44 RT patients. We assessed LV function using pulsed‐wave Doppler ultrasound. Diastolic dysfunction was defined when the E:A ratio was <1. Results Independent predictors of NT‐proBNP levels were age, creatinine, and albumin in CKD patients and age and urea in RT patients. Determinants of SDMA in CKD patients were glomerular filtration rate (GFR) and NT‐proBNP and creatinine in RT patients. In RT patients with diastolic dysfunction, NT‐proBNP and SDMA were significantly higher than in patients without diastolic dysfunction (F = 7.478, P < 0.011; F = 2.631, P < 0.017). After adjustment for GFR, the differences were not seen. In CKD patients adjusted NT‐proBNP and SDMA values for GFR were not significantly higher in patients with diastolic dysfunction than in patients without diastolic dysfunction. Conclusions NT‐proBNP is useful for detection of LV diastolic dysfunction in RT recipients. When evaluating both NT‐proBNP and SDMA it is necessary to consider GFR as a confounding factor.